Grassroots (Economic) Activism in Times of Crisis: Mapping the Redundancy of Collective Actions - Giacomo D’Alisa (Coordinamento SIBA, 2015)
In the current economic crisis of industrialized society, social movements face two types of challenges: firstly, they are confronting institutions that are less capable of and have no propensity for mediating new socio-economic demands; secondly, they are experiencing difficulties in building strong and lasting bonds of solidarity and cooperation among people. The latter are fundamental resources for the emergence of collective action; however, the highly individualized structure of contemporary society makes the creation of social ties ever the more difficult. As a consequence, contemporary waves of protest are often short-lived. Nonetheless, in response to the multidimensional crises, the consolidation of grassroots mutualistic and cooperative experiences, within which new affiliations for collective action are experienced, is on the rise. Indeed, it is a fact that even though conditions are not favorable, social movements have continued to ex-pand and promote community-led initiatives for social and economic sustainability. In some cases, these initiatives play a decisive role in the fight against poverty and in guaranteeing human livelihood. Solidarity-based exchanges and networks, such as barter groups, urban gardening, new consumer-producer networks and cooperatives, time banks, local savings groups, urban squatting, and others similar experiences are typical examples of continuous reactivation of people's desire to be agents of their own destiny. This combination of formal and informal networks are a testimony to an ability and an aspiration. Indeed, on one hand, they are indicative of citizens' capacity to self-organize in order to tolerate, absorb, cope with and adjust to the environmental and social threats posed by neoliberal policies. On the other hand, they are attempting to change an economic system, increasingly perceived as unfair and ecological disruptive, by building an alternative in the cracks of the former, based on greater mutual solidarity between individuals and more sustainable connections with the environment. This special issue is a reflection, among the many that have being proposed of late, on some of these self-organized collective actions that have pass through and/or emerged from the aftermath of the crisis. It is the result of an attempt to cross various disciplinary fields, in order to explore the redundancy of their respective explanations as to why and how some grassroots activities last and succeed, and turn this redundancy into the powerhouse for relaunching more robust and less aleatory initiatives.